2010
DOI: 10.1007/s11199-010-9750-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Portrayals in Indian Television Ads

Abstract: 318 randomly selected television ads from India (from 2004) in three different languages (English, Hindi, and Tamil) were content analyzed to examine both the frequency of appearance and prevalence of gender stereotypes. Results indicate that there are more male than female central characters and voiceovers in Indian ads; stereotypical differences were also found in the type of credibility used by men and women, and the nature of the products they advertised and settings that males and females appeared in. Fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 50 publications
(83 reference statements)
2
60
3
3
Order By: Relevance
“…Summarising key findings from comparable studies across five continents, Furnham and Mak (1999) noted that while male characters have traditionally outnumbered female characters in television advertising, women are now more evident in key visual roles and there is currently some inconsistency in the international research on this issue (Das, 2011). However, women remain concentrated in product categories relating to the home, food preparation, personal care and the body, while men are more often seen in advertisements for financial products (Ganahl, Prinsen & Netzley, 2003, US) and non-domestic products, particularly those related to automobiles and sports (Bartsch et al, 2000;Ganahl et.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Summarising key findings from comparable studies across five continents, Furnham and Mak (1999) noted that while male characters have traditionally outnumbered female characters in television advertising, women are now more evident in key visual roles and there is currently some inconsistency in the international research on this issue (Das, 2011). However, women remain concentrated in product categories relating to the home, food preparation, personal care and the body, while men are more often seen in advertisements for financial products (Ganahl, Prinsen & Netzley, 2003, US) and non-domestic products, particularly those related to automobiles and sports (Bartsch et al, 2000;Ganahl et.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…This prevalence indicates that South African advertisers feature female portrayals that do not fit into commonly identified categories. While previous studies indicated an "other" category (Das 2011;Ferguson et al 1990;Milner and Higgs 2004;Sullivan and O'Connor 1988), they did not explore the depictions within it. In this study, the exploration of "other" portrayals identified four new female roles: leisure woman, sportswoman, spokesperson and customer; each representing newly portrayed, atypical dimensions of the modern South African woman.…”
Section: "Other" Portrayals In Magazine and Television Advertisingmentioning
confidence: 95%
“…Table 1 presents a summary of role categories over the decades since the 1970s (focusing on portrayals of adults). (Bretl and Cantor 1988;Ferrante et al 1988;Sullivan and O'Connor 1988) (Ferguson et al 1990;Mazzella et al 1992;Mwangi 1996;RudanskyKloppers 1991;Siu and Au 1997;Wee et al 1995) (Bolliger 2008;Collins 2011;Das 2011;Furnham and Paltzer 2010;Koerning and Granitz 2006;Milner 2005;Plakoyiannaki and Zotos 2009;Razzouk et al 2003 (Ferguson et al 1990;Mazzella et al 1992;Siu and Au 1997;Wee et al 1995) (Das 2011;Furnham and Paltzer 2010;Milner 2005) The categories in Table 1 Some studies note a category of "other"; however, none reports further examination of the depictions within it. The "other" category thus represents an opportunity to analyse atypical depictions and possibly reveal new roles.…”
Section: An Overview Of Research On Gender Roles In Advertisingmentioning
confidence: 99%
See 1 more Smart Citation
“…Se trata de un área importante dentro del estudio de las diferencias de género en los medios de comunicación, ya que tradicionalmente se ha asociado la masculinidad con el deporte (Aulette, Wittner y Blakely, 2009). Y son muchos los estudios que han reconocido que la representación de mujeres y hombres en los medios de comunicación se hace de forma estereotipada según el género (cfrs., Arima, 2003;Das, 2011;Furnham y Mark, 1999;Paek et al, 2011;Prieler et al, 2011).…”
Section: El Porcentaje De Mujeres Y Hombres Como Figuras Centrales Deunclassified